A self-activated and protective module enhances the preclinical performance of allogeneic anti-CD70 CAR-T cells - Zhang, Zhao; Zhao, Lianfeng; Huang, Tinghui; Chen, Zhengliang; Zhao, Yaoyao; Liang, Junqing; Ao, Xudong; Jia, Xiaoqiong; Kang, Lei; Kong, Linghui; Jing, Qi; Hu, Jianhua; et al. (Frontiers in Immunology, 2025)
IntroductionAllogeneic chimeric antigen receptor T (CAR-T) therapy, also known as universal CAR-T (UCAR-T) therapy, offers broad applicability, high production efficiency, and reduced costs, enabling quicker access for patients. However, clinical application remains limited by challenges such as immune rejection, and issues with potency and durability.MethodsWe first screened a safe and effective anti-CD70 scFv to construct anti-CD70 CAR-T cells. Anti-CD70 UCAR-T cells were then generated by knocking out TRAC, B2M, and HLA-DRA. To address the limitations of UCAR-T therapy, we developed an 'all-in-one' self-activated and protective (SAP) module, integrated into the CAR scaffold. The SAP module consists of the CD47 extracellular domain, a mutant interleukin 7 receptor alpha (IL7Rα) transmembrane domain, and the IL7Rα intracellular domain, designed to protect UCAR-T cells from host immune attacks and enhance their survival. ResultsSAP UCAR-T cells demonstrated significantly reduced immune rejection from the innate immune system, as evidenced by enhanced survival and functionality both in vitro and in vivo. The modified UCAR-T cells exhibited improved persistence, with no observed safety concerns. Furthermore, SAP UCAR-T cells maintained process stability during scale-up production, indicating the potential for large-scale manufacturing.DiscussionOur findings highlight the SAP module as a promising strategy for the preclinical development of anti-CD70 UCAR-T, paving the way for an 'off-the-shelf' cell therapy product.